High Taxes in Hard Times: How Denmark Built and Maintained a Huge Income Tax - Steffen Ganghof (Max Planck Institute for the Study of Societies, 2005)
Denmark is a welfare state whose income tax burden is larger than the total tax burden of the United States or Japan. Given recent political science accounts of the links between tax mixes and the welfare state, Denmark seems to be a puzzling anomaly. These accounts see income taxation as inherently problematic and claim that 'regressive taxes' (social security contributions and indirect consumption) have been conducive to building and maintaining large tax/welfare states. This article provides a simple explanation of the ?Danish puzzle? and challenges the argument about tax mixes. What is problematic about income taxation is capital income taxation, but low income taxes are only one of two ways to keep the capital income tax burden moderate. The other is to differentiate the tax burdens for capital and labor within the income tax. The article also explores the politics of income tax differentiation and suggests that Denmark's high level of income taxation made it easier to maintain and even increase this level in the 1980s and 1990s. – – Die Einkommensteuerlast des Wohlfahrtsstaates Dänemark ist größer als die Gesamtsteuerlast der USA oder Japans. Im Lichte neuerer politikwissenschaftlicher Theorien über den Zusammenhang zwischen Steuermix und Größe des Wohlfahrtsstaates erscheint Dänemark als rätselhafte Anomalie. Die Besteuerung der Einkommen wird als inhärent problematisch angesehen und ?regressive Steuern? (Sozialabgaben und indirekte Konsumsteuern) sollen Wachstum und Widerstandsfähigkeit des Wohlfahrtsstaates begünstigt haben. Dieses Discussion Paper liefert eine einfache Erklärung des dänischen Rätsels und relativiert die Bedeutung des Steuermix: Die Einkommensbesteuerung ist problematisch im Hinblick auf die Besteuerung der Kapitaleinkommen, aber die Senkung der Einkommensteuer ist nur einer von zwei Wegen, die Steuerlast der Kapitaleinkommen zu begrenzen. Der andere Weg besteht in der Differenzierung der Steuerlast für Arbeit und Kapital innerhalb der Einkommensteuer. Das Discussion Paper analysiert die Politik der Einkommensteuerdifferenzierung und argumentiert, dass das hohe Ausgangsniveau der Einkommensteuerlast eine Erhaltung oder gar Erhöhung dieses Niveaus in den 1980er und 1990er Jahren erleichtert hat.
Keywords: 300